EFEKTIVITAS SETELAH PEMBERIAN PUTIH TELUR AYAM DAN SUSU SKIM UNTUK PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - agustin, Sefentina; Dian Purnama Putri (Universitas Batam, 2024)
It is estimated that 70% of women in Indonesia experience perineal injury during the birth process and around 0.5-7% experience trauma to the anal sphincter. If the perineal suture wound does not heal quickly and hygiene is not properly maintained, the perineal area can become pathological, such as infection due to the entry of microorganisms into the perineal wound. Perineal rupture is an injury to the birth canal that occurs during the birth of a baby, whether using an instrument or not using an instrument. In Asia, perineal rupture in society accounts for 50% of the incidence of perineal rupture in the world (Sigalingging & Sikumbang, 2019 ). From data in Puser Village, Tirtayasa District, Banten, from July to September 2022, the number of normal births was 76 patients. In general, all new wounds, episiotomy areas or perineal wounds take 6 to 7 days to heal. Infection not only inhibits the wound healing process but can also cause damage to supporting cell tissue. Albumin has the highest protein content in blood plasma, reaching levels of 60%. Albumin functions to speed up the recovery process of split or damaged body cell tissue, where albumin has a very strong effect in healing wounds. Experimental quantitative research method, two group post test only design. The results of the study concluded that this research was effective for healing grade II perineal wounds in postpartum mothers with a p-value of 0.000 (<0.05), which means there is effectiveness